New trends of Community-Based Tourism management in People's Republic of China - Alip Suroto; Donny Juliandri Prihadi; Eka Kadharpa; Muhammad Azizurrohman; Deasy Silvya Sari (Journal of Enterprise and Development (JED), 2023)
Purpose — This research investigates emerging trends in community-based tourism (CBT) management in the People's Republic of China (PRC), aiming to foster sustainable tourism development. It comprehensively examines evolving strategies, challenges, and opportunities, considering community engagement, empowerment, and sustainable practices in China's distinct socio-cultural and economic context.Method — Employing a qualitative approach, this research draws on case studies and expert insights to provide a holistic view of current community-based tourism management in China. The analysis involves literature review, stakeholder interviews, and examination of successful CBT projects across diverse regions.Result — The paper reveals significant trends in PRC's community-based tourism management, including tech integration, personalized experiences, sustainable resource practices, and cultural preservation. These trends are explored via practical examples, showcasing their impact on communities and tourists.Contribution — This research enriches the understanding of evolving CBT management in China by spotlighting recent trends and their consequences. It offers insights into innovative strategies fostering tourism, cultural heritage preservation, and sustainability. The paper is a valuable resource for policymakers, practitioners, and researchers interested in sustainable tourism and community engagement in the PRC and beyond.